Adolescent Eating Disorder Day Programme Treatment Models and Outcomes: A Systematic Scoping Review - Baudinet, Julian; Simic, Mima (Frontiers in Psychiatry, 2021)
Background: Adolescent eating disorder day programmes (DP), or partial hospitalisation programs, are becoming increasingly widespread worldwide. They typically function as an alternative to inpatient care and/or a step up or down in treatment intensity. While there are now numerous programmes operating internationally, there is large variability in the content, structure and theoretical underpinnings of each programme. This makes it difficult to compare programme outcomes, and the impact the therapeutic model may have. Aims: To review existing literature on adolescent eating disorder DP treatment models and outcomes. Methods: A systematic scoping review was conducted. Four databases (PsychInfo, EMBASE, Medline, CENTRAL) were searched for relevant peer-reviewed journal articles and book chapters investigating adolescent eating disorder DPs that function as alternatives to inpatient treatment. No restrictions on study methodology were imposed. Studies were first mapped by location, study characteristics and day programme treatment characteristics, then narratively synthesized. Results: Forty nine studies were included in this review. All used a quantitative methodology. One study also included qualitative methods. The majority of studies included describe DPs in the USA (69%). Seventy-six percent described DPs that operate five-days per week and most (57%) only admit or only report on outcomes for people with restrictive eating disorders. Sixty-nine percent prioritised family involvement within their therapeutic model. The remainder were more informed by individual psychotherapeutic models. Generally, DP treatment is associated with weight gain and improvements in eating disorder and comorbid psychopathology. The studies that include follow-up data (27%) reveal improvements are usually maintained from three months to two years post-treatment. Early weight gain, early psychological change and early therapeutic alliance are associated with improved end of treatment outcomes. Findings regarding other potential predictors of outcome are mixed. Conclusions: Current evidence suggests day programmes are an effective alternative to inpatient treatment that lead to sustained improvements. DPs tend to either be young-person-only with a family-focused treatment model or all age with a more integrative model. Controlled, empirical investigations into the impact of the therapeutic model on outcomes are needed, as are investigations into treatment mechanisms and the individual and parent experience of day programme treatment.